PENINGKATAN KESEHATAN PADA REMAJA TENTANG REPRODUKSI SEHAT MENUJU GENERASI HEBAT - Maimaznah Maimaznah; Iin Indrawati (Jurnal Abdimas Kesehatan (JAK), 2019)
Teenagers generally face problems about sexuality and reproductive health due to limited information and advocacy, no access to friendly services to adolescents, limited institutions in the government that handle adolescents in particular, there is no law that accommodates adolescent rights, and there is no health curriculum reproduction in adolescents. The results of the survey in Karang Kota Village found that there were still many adolescents who did not know about reproductive health, there were incidents of teenagers becoming pregnant outside of marriage and getting married at a young age (˂20 years). The target and outcome of this community service activity are adolescents who obtain appropriate information about reproductive health and understand and can carry out in their daily lives to improve adolescent health, especially reproductive health. The stages carried out in this activity include: 1). conduct a survey to the location (Kota Karang Village, Kumpeh Ulu District), 2). looking for information about adolescent health in Kota Karang Village, Kec. Kumpeh Ulu, 3). do health promotion in Kota Karang Village, Kec. Kumpeh Ulu, and 4). conduct an evaluation of the promotion carried out. Teenagers get the right information about reproductive health and understand and can carry out in daily life to improve adolescent health, especially reproductive health.